A millimeter‐wave scalable small‐signal modeling approach based on FW‐EM for AlGaN/GaN HEMT up to 110 GHz. Issue 8 (1st May 2020) - Zhu, Guiqiang; Chang, Chen; Xu, Yuehang; Zhang, Ziheng; Al‐saman, Amgad A.; Lin, Fujiang
Abstract: A new scalable small‐signal model for 0.1 μm AlGaN/GaN HEMT up to 110 GHz is presented in this paper. The taps between the gate/drain manifold and fingers on the device has been investigated and included in the equivalent circuit. In addition, to ensure high scalability, a set of scaling rules are presented. A novel extraction procedure for extrinsic capacitances using full‐wave electromagnetic (FW‐EM) method has been introduced along with corresponding structures used for EM simulation. The nonlinear dependence of the extrinsic inductances on the gate‐width has been accounted for by a new scaling rule, which can be used to extract their value from measurement data. To guarantee the stability of the scaling coefficients, two devices with different gate‐width have been utilized for their generation. The proposed scalable model has been verified using 0.1 μm AlGaN/GaN HEMT devices with different gate‐widths and different gate‐fingers. The experiment results show good agreement between model and measurement S‐parameters up to 110 GHz.